Candida bloodstream infection among children hospitalized in three public sector hospitals in the Metro West region of Cape Town, South Africa - Gebremicael, Mulugeta Naizgi (Department of Paediatrics and Child Health, 2023)
Introduction Candida bloodstream infection (BSI) causes appreciable mortality in children. There are few studies describing the epidemiology of Candida BSI in children living in the Western Cape province of South Africa. Methods A retrospective descriptive study was conducted at three public sector hospitals in Cape Town from January 2015 to December 2019. Demographic, clinical, antifungal management and patient outcome data were obtained by medical record review. Candida species and antifungal susceptibility results were extracted from the National Health Laboratory Service microbiology database Results Of the 97 Candida BSI episodes identified during the study period, 48/97 (49.5%) were C. albicans, 49/97 (50.5%) non-C. albicans species. The overall incidence risk was 0.84 Candida BSI episodes per 1000 admissions at Red Cross War Memorial Children's Hospital. Of the 77 Candida BSI episodes with available clinical information, median age (interquartile range) at the time of BSI was 6.8 (1.3-24.7) months, 46.8% were associated with moderate or severe underweight-for-age and vasopressor therapy was administered to 22 (28.6%) participants. Fluconazole resistance was documented among 25% and 0% of non-C. albicans and C. albicans isolates respectively. All Candida isolates tested were susceptible to amphotericin B and the echinocandins. The mortality rate within 30 days of BSI diagnosis was 17.3% (13/75). On multivariable analysis, concomitant bacterial infection during Candida BSI was associated with 30-day mortality, adjusted OR 5.7, 95% confidence interval: 1.4-24.0. Conclusion The study adds to the limited number of studies describing paediatric Candida BSI in sub Saharan Africa. Concomitant bacterial infection was associated with 30-day mortality.